2021
DOI: 10.1038/s42003-021-02677-y
|View full text |Cite
|
Sign up to set email alerts
|

In vitro CSC-derived cardiomyocytes exhibit the typical microRNA-mRNA blueprint of endogenous cardiomyocytes

Abstract: AbstractmiRNAs modulate cardiomyocyte specification by targeting mRNAs of cell cycle regulators and acting in cardiac muscle lineage gene regulatory loops. It is unknown if or to-what-extent these miRNA/mRNA networks are operative during cardiomyocyte differentiation of adult cardiac stem/progenitor cells (CSCs). Clonally-derived mouse CSCs differentiated into contracting cardiomyocytes in vitro (iCMs). Comparison of “CSCs vs. iCMs” mRNome and microRNome showed a balanced up-regulation of CM-related mRNAs toge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 110 publications
1
33
0
Order By: Relevance
“…When placed in laminin-coated plastic dishes with LIF-deprived basic differentiation medium for 14 days, the peripheral cells of the spheres expressed high levels of smooth muscle as well as endothelial and cardiac lineages. Nevertheless, the CM derived from cloned CSCs still reach a biochemical myogenic differentiation that is intermediate between fetal and neonatal cardiomyocytes [150]. These data have also been confirmed by RNASeq expression profile analysis.…”
Section: From Cardiac Spheroids To Cardioidssupporting
confidence: 53%
See 1 more Smart Citation
“…When placed in laminin-coated plastic dishes with LIF-deprived basic differentiation medium for 14 days, the peripheral cells of the spheres expressed high levels of smooth muscle as well as endothelial and cardiac lineages. Nevertheless, the CM derived from cloned CSCs still reach a biochemical myogenic differentiation that is intermediate between fetal and neonatal cardiomyocytes [150]. These data have also been confirmed by RNASeq expression profile analysis.…”
Section: From Cardiac Spheroids To Cardioidssupporting
confidence: 53%
“…Comparison of transcriptome and miRNome between clonal CSCs, contracting cardiomyocytes obtained from CSC-derived cardiospheres (iCMs), and adult cardiomyocytes (aCMs) has shown that CSCs are cardiomyogenic since they activate the entire gene network and specific cardiomyo-miRs characteristic of the aCMs phenotype. Yet, in concordance with the immature phenotype of iCMs, the expression of these miRNAs is still significantly lower than in aCMs, falling between CSCs and aCMs [150]. Cardiosphere attachment on laminin or 0,1% gelatin plates alters cell shape and geometry, leading to cell flattening and changes in the cytoskeleton and nuclear shape.…”
Section: From Cardiac Spheroids To Cardioidsmentioning
confidence: 95%
“…Adult CSCs are multipotent, and when grown in a specific differentiation medium acquire the phenotype of the three main cardiac cells (cardiomyocytes, smooth muscle and endothelial cells). However, cardiomyocyte derived from clonal CSCs showed a phenotype that more closely resembles neonatal, immature cardiomyocytes compared with the adult, terminally differentiated cardiomyocytes [ 89 ]. Contracting cardiomyocyte derived from clonal CSCs have an intermediate transcriptional profile with the levels of mRNA of transcription factors and myofilament proteins that fall between fetal and neonatal cardiomyocytes.…”
Section: Diabetes and Cardiac Stem Cell Biologymentioning
confidence: 99%
“…Cardiomyocyte derived from CSCs up-regulate the cardiomyo-miRs (miR-1a 3p, miR-133a-1, miR-133a-2, miR-204, miR-335, miR-486, miR-490, and miR-499) to a lower extent than adult cardiomyocytes. However, the specific networks of miRNA/mRNAs operative in CSC-derived cardiomyocytes closely resembled those of adult cardiomyocytes [ 89 ].…”
Section: Diabetes and Cardiac Stem Cell Biologymentioning
confidence: 99%
“…The transmission of dyes via gap junctions between CSCs and CMs or fibroblasts was demonstrated previously and verified the functional coupling of these three cell populations[ 97 ]. In addition, micro ribonucleic acid (miRNA-499) translocates from CMs to CSCs comprising to the initiation of lineage specification and formation of myocytes[ 103 ].…”
Section: Transcriptome and Regenerative Capacity Of Sub-populationsmentioning
confidence: 99%